160 A CLOSED-LOOP AUDIT EXAMINING THE USE OF PROPHYLACTIC ANTI-COAGULATION IN OLDER ADULTS ADMITTED TO A SPECIALIST GERIATRIC SERVICE. (25th October 2022) - Brar, SK; Sheehan, O; Martin, R; Rasheed, M
Abstract: Background: Guidelines recommend prescription of Prophylactic Anticoagulation (PA) to all hospitalized older adults unless a contraindication exits. In many cases this does not happen at the time of admission increasing the risk of thromboembolic events. We aimed to assess the use of PA across the medicine for the geriatric service of a level 3 hospital (average daily census of service 120) then use quality improvement to achieve our goal of 95% prescription of prophylactic anticoagulation when appropriate. Methods: Medication kardexes and clinical notes were reviewed to collect variables including age, length of stay, creatinine clearance, weight, mobility status, use and dose of antithrombotic medications and documentation of reason if not prescribed. Following initial data collection, cause and effect analysis was performed to identify reasons for under-prescription and small tests of change were conducted across 4 PDSA cycles before data collection was repeated. Results: Initial data collection revealed that only 80% of older adults admitted to the service were receiving prophylactic anticoagulation. Cause and effect analysis identified many reasons for failure to prescribe PA including inadequate history taking, lack of clinician education and training, poor documentation, lack of handover between clinicians, failure to complete medication reconciliation on admission and lack of pharmacy support on some wards. Each of these contributory factors were addressed in turn. After a month of QI activities prescription of PA improved to 83% and by 3 months 98.1% (104/106) of patients were receiving PA with only 2 patients for whom PA was not prescribed without clear documentation of the reason. Conclusion: Sustained quality improvement resulted in a culture change across our service improving rates of appropriate prescription of PA and raising the quality of care delivered to older adults. This model of quality improvement is now being replicated across our department to address other gaps in service delivery.